1992
DOI: 10.1063/1.107077
|View full text |Cite
|
Sign up to set email alerts
|

X-ray generation by high irradiance subpicosecond lasers

Abstract: We have studied the interaction of 290-fs, 308-nm laser pulses with aluminum targets at irradiances exceeding 5×1018 W/cm2. The x-ray spectrum is dominated by the H- and He-like lines from aluminum, with the brightest lines radiating 0.8% of the incident laser light energy. This fraction is close to that measured at 50 times less irradiance, but occurs at a slightly higher ionization stage. The x rays are emitted from a region of subcritical electron density at 3–6×1021 W cm−3. The radiance of the 1.73-keV Lα … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Over the past two decades several experiments have been performed to determine x-ray yield and conversion efficiency as a function of laser irradiance, wavelength, and pulse duration. [3][4][5][6][7][8] In addition, the drastic decrease in x-ray conversion efficiency with heavier target materials has been demonstrated experimentally. [9][10][11] The problem encountered by an experimentalist designing an x-ray backlighter source is the scarcity of data points and the confusion created by discrepancies in the available data.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades several experiments have been performed to determine x-ray yield and conversion efficiency as a function of laser irradiance, wavelength, and pulse duration. [3][4][5][6][7][8] In addition, the drastic decrease in x-ray conversion efficiency with heavier target materials has been demonstrated experimentally. [9][10][11] The problem encountered by an experimentalist designing an x-ray backlighter source is the scarcity of data points and the confusion created by discrepancies in the available data.…”
Section: Introductionmentioning
confidence: 99%
“…Some of this experimental work has previously been done. [2][3][4][5][6][7][8][9][10][11] The problem encountered by the experimentalist is that the number of data points is limited and those that do exist often disagree. In some cases discrepancies can be explained by the differences between lasers (in particular the far field distribution).…”
Section: Introductionmentioning
confidence: 99%
“…One of the authors (G.T.S.) with his collaborators has shown that KrF and XeC1 lasers can generate He-and H-like Aluminum line radiation in the 1.5-1.8 keV spectral range and thus generate intensities on those lines of the order of 1014W/cma at the target [6,7]. With such light sources, an experimental study of multi-photon ionization of inner shell electrons might be possible.…”
Section: Introductionmentioning
confidence: 96%